A field guide for science writers the official guide of the National Association of Science Writers (Oxford Univ. Press, 1997)
In a Field Guide for Science Writers, the official guide of the National Association of Science Writers, budding journalists and veteran reporters have a superb roadmap to this exciting area of journalism. Here some three dozen of the best-known science writers in America share their hard-earned knowledge on how they do their job. Boyce Rensberger describes how he covers stories for the Washington Post; two-time Pulitzer Prize-winner and New York Times reporter John Noble Wilford outlines the pitfalls and rewards of writing full-length books on scientific topics; NPR's Ira Flatow tells how radio pieces combine ambient sounds, music, voices, and facts to create a mental picture and evoke the feeling of "being there"; and Pulitzer prize-winning journalist Laurie Garrett, author of the bestselling The Coming Plague, discusses how to cover, and survive, a deadly epidemic. Each article brims with detailed, nuts-and-bolts information.